PHARMACEUTICAL PATENT PROTECTION VERSUS NATIONAL DRUG POLICY IN SOUTH AFRICA: A TENSION BETWEEN INTERNATIONAL STANDARS AND DOMESTIC DEVELOPMENTAL POLICY - Tomi Suryo Utomo (Fakultas Hukum Universitas Gadjah Mada, 2007)
Abstract